Strategic and Tactical Asset Allocation An Integrated Approach - Lumholdt, Henrik (Springer International Publishing, 2018)
This book covers each step in the asset allocation process, addressing as many of the relevant questions as possible along the way. How can we formulate expectations about long-term returns? How relevant are valuations? What are the challenges to optimizing the portfolio? Can factor investing add value and, if so, how can it be implemented? Which are the key performance drivers for each asset class, and what determines how they are correlated? How can we apply insights about the business cycle to tactical asset allocation? The book is aimed at finance professionals and others looking for a coherent framework for decision-making in asset allocation, both at the strategic and tactical level. It stresses analysis rather than pre-conceived ideas about investments, and it draws on both empirical research and practical experience to give the reader as strong a background as possible.